The clinical and economic burden of pneumonia in patients enrolled in Medicare receiving dialysis: a retrospective, observational cohort study. Issue 1 (December 2016) - Sibbel, Scott; Sato, Reiko; Hunt, Abigail; Turenne, Wendy; Brunelli, Steven
Abstract Background End-stage renal disease (ESRD) patients receiving dialysis are at particular risk for infection. We assessed the clinical and economic burden of pneumonia in a population of Medicare-enrolled ESRD patients with respect to incidence and case fatality rates, rates of all-cause and cardiovascular hospitalization, and costs. Methods Patients received dialysis between 01 January 2009 and 31 December 2011 and were enrolled in Medicare Parts A and B. Pneumonia episodes were identified from institutional and supplier claims. Patients were considered at-risk from first date of Medicare coverage and were censored upon transplant, withdrawal from dialysis, recovery of renal function, loss of Medicare benefits, or death. Linear mixed-effects models were used to assess hospitalization rates and costs over the 3 months prior to and 12 months following pneumonia episodes. Results The pneumonia incidence rate for the study period was 21.4 events/100 patient-years; the majority of episodes (90.1%) required inpatient treatment. The 30-day case fatality rate was 10.7%. Compared to month -3 prior to event, rates of all-cause and cardiovascular hospitalization were higher in the month of the pneumonia episode (IRR, 4.61 and 4.30). All-cause admission rates remained elevated through month 12; cardiovascular admission rates remained elevated through month 6. Mean per-patient per-month costs were $10, 976 higher in the month of index episode compared to month -3, largely driven by increased inpatient costs, and remained elevated through end of 12-month follow-up. Conclusion Pneumonia episodes are frequent among ESRD patients and result in hospitalizations and greater overall costs to Medicare over the following year.